K-Drama Excessive Watching Behavior and Loneliness of Parasocial Interaction in College Students - Saptari, Saptari; Suhesty, Aulia; Rasyid, Miranti; Handayani, Nanik (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. The emergence of the Korean Wave, encompassing K-dramas and K-pop, has garnered significant interest, particularly among college students. This research investigates how excessive viewing and feelings of loneliness impact social interactions. Utilizing a quantitative research design, the study involved 83 students from the Faculty of Social and Political Sciences at X University, selected through probability sampling methods. Data collection methods included scales measuring parasocial interactions, excessive viewing habits, and loneliness levels. The analysis employed multiple linear regression techniques. Key findings indicate that: (1) excessive viewing and loneliness significantly affect parasocial interactions, with an F-value of 3.992 exceeding the F-table value of 3.18 and a p-value of 0.001, contributing an influence of 42.1% (R²); (2) excessive viewing positively correlates with parasocial interactions, shown by a beta coefficient (β) of 0.377, a t-value of 2.071 surpassing the t-table value of 2.008, and a p-value of 0.044 (p < 0.05); (3) however, loneliness does not significantly impact parasocial interactions, evidenced by a beta coefficient (β) of 0.156, a count of 0.156.859 falling below the t-table value of 2.008, and a p-value of 0.395 (p < 0.05). Keywords: Social interaction, excessive watching, loneliness. Abstrak. Perkembangan fenomena Korean Wave, yang mencakup K-Drama dan musik K-Pop, telah menarik perhatian yang luas, khususnya di kalangan mahasiswa. Penelitian ini bertujuan untuk mengeksplorasi dampak dari menonton secara berlebihan dan perasaan kesepian terhadap interaksi parasosial. Metode yang digunakan dalam penelitian ini adalah pendekatan kuantitatif. Subjek penelitian terdiri dari 83 mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas X yang dipilih melalui teknik probability sampling. Pengumpulan data dilakukan dengan menggunakan skala untuk mengukur interaksi parasosial, tingkat menonton berlebihan, dan kesepian. Analisis data dilakukan menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa: (1) terdapat pengaruh signifikan antara menonton berlebihan dan kesepian terhadap interaksi parasosial, dengan nilai F hitung sebesar 3.992 yang lebih besar dari F tabel 3.18 dan nilai p sebesar 0.001, serta kontribusi pengaruh (R²) mencapai 42.1%; (2) terdapat pengaruh positif yang signifikan dari menonton berlebihan terhadap interaksi parasosial dengan nilai koefisien beta (β) sebesar 0.377, t hitung 2.071 lebih besar dari t tabel 2.008, dan nilai p sebesar 0.044 (p < 0.05); (3) tidak ditemukan pengaruh signifikan dari kesepian terhadap interaksi parasosial dengan nilai koefisien beta (β) sebesar 0.156, t hitung 0.859 lebih kecil dari t tabel 2.008, dan nilai p sebesar 0.395 (p < 0.05).Kata Kunci: Interaksi parasosial, menonton berlebihan, kesepian.